Effect of immersion time in sour turmeric drinks on colour changing of heat cured acrylic resin plate - Kusmawati, Fransiska Nuning; Setyaputri, Nandini (Universitas Padjadjaran, 2021)
ABSTRACTBackground: Heat cured acrylic resin is a material that is often used as a denture base, The most common problem faced by heat cured acrylic resins is discoloration. Heat cured acrylic resin has the property of absorbing water slowly. One of the health drinks that has the potential for discoloration in heat cured acrylic resin is the packaging of sour turmeric packaging, because turmeric (Curcuma domestica Val.) in this drink contains yellow curcuminoid. Objective: To study and explain the effect of immersion of packaged turmeric drinks on the color change of heat cured acrylic resin plate. Method: Experimental study with control group pre-test and post-test design. The number of samples was 32 samples of heat cured acrylic resin plates, the samples were divided into 2 groups, the control group and the treatment group, each of group was 16 samples. Then 32 of these samples were immersed in distilled water and sour turmeric for 7 days and 7 days + 7 days. Data analysis was performed by Friedman test and Mann Whitney test. Results: The results of the Friedman test showed a significant color change in the heat cured acrylic resin plate immersed in turmeric drinks during before, after 7 days and after 7 days + 7 days, especially on the value of chrome and hue. The results of the Mann Whitney test showed that there were significant differences in the heat cured acrylic resin plate after immersion in distilled water solution and packaged sour turmeric drinks for 7 days and 7 days + 7 days especially in the chrome and hue values. Conclusion: The color change effect of heat cured acrylic resin plate immersed in sour turmeric drink for 7 days + 7 days is more influential than immersed for 7 days.Keywords: sour turmeric drink packaging, heat cured acrylic resin, color change